Estudos sobre o uso medicinal da Cannabis: uma análise a partir do campo informacional - Semensato, Camilo Ramos (2023)
Cannabis, popularly known in Brazil as "marijuana", has been used culturally by humans for millennia. It is indicated that, currently, its use is associated with several purposes: medicinal, gastronomic, industrial and social (known as "recreational", and also named as "adult use"). This research presents from a historical perspective, the social developments of the illegality of Cannabis, the cultural context of Cannabis, in addition to the industrial use and medicinal use of Cannabis. Particularities about the development of science, the characteristics of scientific communication and the development of scientific journals are discussed. This research found answers, in scientific periodicals specialized in Cannabis, regarding the status of its medicinal use. As for the method used to identify the universe to be researched, it allowed the identification of scientific journals in Ulrich's, which has an editorial scope focused on Cannabis studies, available in open access, namely: [1] Cannabis, [2] Cannabis and Cannabinoid Research, [3] Journal of Cannabis Research and [4] Medical Cannabis and Cannabinoids. In addition, it was confirmed that the pathways that characterize open access publications expand the reach of scientific communication and optimize access to the publications themselves, also amplify the social value of research, the value of funding agencies and research institutions. The reading and analysis of the keywords, title and abstract of each material allowed the identification of thematic nuclei of the documents, enabling the creation of categories of analysis according to Bardin's (1977) proposal. The following research themes were identified: treatment of pain of different origins; use of cannabinoids as substitutes for other medications; management of endometriosis; treatment for arthritis; treatment of inflammatory bowel diseases; treatment for sickle cell disease; treatment for cachexia; treatment for refractory stuttering; treatment for anxiety; medicinal use of Cannabis for COVID-19; self-medication with Cannabis; treatments for Cannabis overuse disorders; drug interactions; cannabidiol (CBD); other cannabinoids; chemical components of Cannabis and its derivatives; perioperative uses of Cannabis; consumption patterns for medicinal purposes; healthcare professionals; patients using Cannabis for medicinal purposes; studies and reviews. It is stated that the therapeutic potential of Cannabis is vast, a fact that allows the topic to assume a significant role in scientific studies soon, as well as to expand its own use in medicine.